The Role of Th17 Cells and IL-17 in Th2 Immune Responses of Allergic Conjunctivitis - Xiang-Tian Meng; Yun-Yue Shi; Hong Zhang; Hong-Yan Zhou (Journal of Ophthalmology)
Allergic conjunctivitis (AC) is a common allergic disease that is often associated with the onset of rhinitis or asthma. The incidence of AC has increased significantly in recent years possibly due to air pollution and climate warming. AC seriously affects patients’ quality of life and work efficiency. Th (T-helper) 2 immune responses and type I hypersensitivity reactions are generally considered the basis of occurrence of AC. It has been found that new subpopulations of T-helper cells, Th17 cells that produce interleukin-17 (IL-17), play an important role in the Th2-mediated pathogenesis of conjunctivitis. Studies have shown that Th17 cells are involved in a variety of immune inflammation, including psoriasis, rheumatoid arthritis, inflammatory bowel disease, systemic lupus erythematosus, and asthma. However, the role of Th17 and IL-17 in AC is unclear. This paper will focus on how T-helper 17 cells and interleukin-17 are activated in the Th2 immune response of allergic conjunctivitis and how they promote the Th2 immune response of AC.